Metal-Free, DTBP-Mediated Methylthiolation of Arylboronic Acids with Dimethyldisulfide - Wu, Xiang-mei; Lou, Jia-ming; Yan, Guo-bing (Synlett, 2016)
An efficient method for the C–S bond formation via the coupling reaction of arylboronic acids with dimethyldisulfide has been developed under the metal-free conditions. This novel protocol provides an attractive route for the synthesis of aryl methyl sulfides, due to its operational simplicity, satisfactory yields, excellent functional-group tolerance, as well as the mild reaction conditions.
Keywords: methylthiolation; arylboronic acids; dimethyldisulfide; aryl methyl sulfides; di-tert-butyl peroxide